Pengaruh Semangat Kerja Terhadap Produktivitas Kerja dan Kompensasi Sebagai Variabel Moderating - Pranowo Adji Yudhistira; Bambang Suhada; Nina Lelawati (Jurnal Manajemen DIVERSIFIKASI, 2026)
The aim of this research is to determine whether there is an influence of work morale on employee performance with compensation as a moderating variable at PT. Marm Maju Sejahtera. Success in company productivity depends on employee morale and the compensation provided. This research uses quantitative research, the sample in this research was 36 employees. The data collection technique uses a questionnaire, with data analysis using Validity Test, Reliability Test, Normality Test, Linearity Test, Homogeneity Test, MRA Interaction Test, R Determination Test, and Statistical Hypothesis Test. By using the data processing program SPSS version 22. The results of the research show that work enthusiasm influences work productivity. Compensation as a moderation variable is able to strengthen work enthusiasm for work productivity at PT. Marm Maju Sejahtera,